The analytical solutions for Volterra integro-differential equations within Local fractional operators by Yang-Laplace transform - Hassan Kamil Jassim (Sahand Communications in Mathematical Analysis, 2017)
In this paper, we apply the local fractional Laplace transform method (or Yang-Laplace transform) on Volterra integro-differential equations of the second kind within the local fractional integral operators to obtain the analytical approximate solutions. The iteration procedure is based on local fractional derivative operators. This approach provides us with a convenient way to find a solution with less computation as compared with local fractional variational iteration method. Some illustrative examples are discussed. The results show that the methodology is very efficient and a simple tool for solving integral equations.